Paediatric cases of Ceylon krait (Bungarus ceylonicus) bites and some similar looking non-venomous snakebites in Sri Lanka: Misidentification and antivenom administration. (30th July 2021) - Namal Rathnayaka, R.M.M.K.; Nishanthi Ranathunga, P.E.A.; Kularatne, S.A.M.
Abstract: Ceylon krait ( Bungarus ceylonicus ) of the family Elapidae is a highly venomous endemic species inhabiting in the wet zone and some parts of the intermediate climatic zones of Sri Lanka. Clinical records of its bites are rare and limited to five case reports in the literature. It is of interest to note that there are several non-venomous snakes in Sri Lanka having similar morphological appearance to kraits causing identification difficulties which lead to unnecessary and unindicated administration of antivenom. We report two paediatric cases of proven Ceylon krait bites and three adult patients with similar looking non-venomous snakebites. These children were 1½ and 13 years old and developed neuroparalysis without progressing to respiratory failure and recovered. Both the children were administered Indian polyvalent antivenom which has not developed against endemic Ceylon krait venom. The two adult patients also received antivenom due to the misidentification without clinical and laboratory evidence of envenoming. Graphical abstract: Image 1 Highlights: Ceylon krait is endemic to Sri Lanka. First case report of describing paediatric Ceylon krait bites. Neuroparalysis is the main clinical feature. 3 cases of similar looking nonvenomous snakebites are described.